Jacobian approximation of the Sum-Alpha stopping criterion - Aissa Ouardi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2025)
This article will report the development of new application of the SumAlpha stopping criterion to the case of log – maximum a posterioru LogMAP turbo decoding. It shows how to adapt Sum-Alphas quantities when using the Log-MAP algorithm and how to deduce a good decision threshold. We apply a logarithm to the quantity Sum-Alpha which is evaluated by the same Jacobian logarithm of the Log-MAP algorithm. We call this new adaptation Jacobian Approximation of Sum-Alpha (JASA) criterion. The simulation results demonstrate that the JASA criterion achieves comparable performance (in terms of bit error rate (BER) and frame error rate (FER)) to the Sum-Alpha and cross-entropy (CE) criteria, with the same average number of iterations.